The Arctic Yearbook - Heininen, Dr. Lassi; Exner-Pirot, Heather; Plouffe, Joël
The arctic Yearbook 2012 is the outcome of the work conducted by the Northern Research Forum and the University of the Arctic Thematic Network (TN) on Geopolitics and Security. The Arctic Yearbook is intended to be the preeminent repository of critical analysis on the Arctic region, with a mandate to inform observers about the state of the Arctic geopolitics and security. The Arctic Yearbook 2012 is accessible on line under limited copyright protection.